2013
DOI: 10.1186/1743-0003-10-69
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and criterion validity of two applications of the iPhone™ to measure cervical range of motion in healthy participants

Abstract: Summary of background dataRecent smartphones, such as the iPhone, are often equipped with an accelerometer and magnetometer, which, through software applications, can perform various inclinometric functions. Although these applications are intended for recreational use, they have the potential to measure and quantify range of motion. The purpose of this study was to estimate the intra and inter-rater reliability as well as the criterion validity of the clinometer and compass applications of the iPhone in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(166 citation statements)
references
References 19 publications
8
143
2
6
Order By: Relevance
“…Reliability estimates very important psychometric properties since before an instrument can be considered valid, it needs to be reliable [6]. Examiner B was chosen for the intrarater reliability because he is the most experienced one.…”
Section: Intra-rater Reliabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Reliability estimates very important psychometric properties since before an instrument can be considered valid, it needs to be reliable [6]. Examiner B was chosen for the intrarater reliability because he is the most experienced one.…”
Section: Intra-rater Reliabilitymentioning
confidence: 99%
“…Laflame et al, [6] who investigate the reliability and validity of i phone in measuring cervical ROM. The results of that study revealed moderate inter-rater reliability for movements in the sagittal (ICCs = 0.48 -0.49).…”
Section: Intra-rater Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The apps used by Yamada et al 26 and Nishiguchi et al 13 demonstrated ''remarkable consistency'' during gait analysis (e.g., peak frequency and acceleration peak intervals) and correlated significantly (r > 0.82) with more traditional triaxial accelerometers. Likewise, the iPhone app used by TousignantLaflamme et al 27 demonstrated good inter-rater reliability and validity when measuring cervical range of motion. The use of these mobile devices has become a growing trend in the field of rehabilitation due to their small size, significant processing power, portability, prevalence in the general population, long battery life, and low cost.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that almost no App can provide a better way to manage chronic disease. Tousignant-Laflamme Yand others [10] was used to analyze the internal and external reliability of two App. The results show that the two App's internal reliability is general, external reliability is low.…”
Section: Mobile Medical App Quality and Contentmentioning
confidence: 99%